Adjuvant Capacity of the Aromatic Geranyl Derivative Filifolinone in Salmonids - Imarai-Bahamonde, C; Modak-Canobra, B; Valenzuela-Montenegro, B; Rodriguez-Tirado, F (Academic Press, 2013)
Sin Resumen Disponible